Validity of the Collective Agreement in Terminating a Fixed Term Employment Agreement According to Labor Law - Michele Fedryca; Rasji (Journal of Law, Politic and Humanities, 2024)
The termination of a fixed-term employment agreement (PKWT) is regulated by applicable laws and regulations, including but not limited to the Employment Law. A PKWT can automatically terminate upon the expiration of the agreed-upon term, or it may also be terminated prior to the specified time if there are valid reasons, such as a breach of contractual provisions, force majeure circumstances, or mutual agreement between the parties. The termination procedure must be carried out in accordance with the provisions written in the agreement, with written notice provided to the other party within a sufficient timeframe for that party to make necessary preparations. Employees are entitled to receive all rights stipulated in the agreement, including but not limited to salary, benefits, and other entitlements, until the last day of employment. Conversely, the employer is obligated to provide valid and clear evidence of termination to avoid disputes in the future. If the termination is conducted in a manner that does not comply with the procedure or without a justifiable reason, the employee has the right to file a lawsuit to claim their entitlements. Therefore, it is essential for both parties to understand and adhere to the provisions contained in the employment agreement and to ensure that there are clear clauses regarding the conditions and procedures for terminating the agreement.